PEMBELAJARAN KITAB TA’LIM AL-MUTA’ALIM UPAYA INTERNALISASI NILAI-NILAI KARAKTER - Yuliana Yuliana (https://www.ejournal.smaamc.sch.id/index.php/belajar, 2023)
Good educational results are characterized by outputs that lead to the realization of morality, and the formation of character in real life. This study uses a descriptive qualitative approach, aimed at describing, and analyzing the planning, implementation, and internationalization model of character values in MTs Miftakhul Huda Bojonegoro. The results of this study are as follows: (1) In planning including; a) material, b) objectives, c) learning methods, and d) analysis of needs in learning. (2) The process of internalizing character values through the study of the book of Ta'lim Al-Mut'allim uses three stages: 1) Transformation of values. At this stage, the focus is on understanding the material value in the book of Ta'lim Al-Mut'allim. 2) Value transactions, This stage occurs two-way mutual interaction between students and teachers actively. 3) The stage of trans-internalization of the character. In this stage, the teacher and students begin to correlate between the character values that are in the book of Ta'lim Al-Mut'allim, which can be carried out in real life